Climate Change and Climate Literacy in India — Some Key Aspects for Consideration in the Curriculum - Shimray, Chong (SCHOOL SCIENCE, 2020)
Climate change is such a threat to human existence that world leaders meet and negotiate to take appropriate measures to address it. Although the Government of India is committed to tackling it, the issue has not caught the attention of its people, and hence it is not a part of daily discourses, not even in educational institutions. A closer look at the existing curriculum reveals that the emphasis given to climate change is inadequate, and climate change is yet to be streamlined in the curriculum. The article provides a perspective on how to incorporate climate change education and the possible challenges to be overcome to bring about climate literacy Climate change is such a threat to human existence that world leaders meet and negotiate to take appropriate measures to address it. Although the Government of India is committed to tackling it, the issue has not caught the attention of its people, and hence it is not a part of daily discourses, not even in educational institutions. A closer look at the existing curriculum reveals that the emphasis given to climate change is inadequate, and climate change is yet to be streamlined in the curriculum. The article provides a perspective on how to incorporate climate change education and the possible challenges to be overcome to bring about climate literacy